(untitled) (Al-Mansour Journal, 2022)
Covid-19 is a virus sweeping all countries of the world like a tornado, but in varying proportions, depending on the health awareness of the country’s population as well as the services and health care provided by the country. Despite the great scientific development in the medical field, there is no effective treatment for the virus or a vaccine that has proven to be highly effective. Therefore, countries need non-medical or clinical solutions to confront the epidemic and control its spread by understanding the behavior of a disease through the use of data mining tools. In this research paper, a k-mediod clustering algorithm was applied to a data set of Covid patients in the Philippines, and the results showed the behavior of a disease by collect data according to the age groups that Covid-19 virus targeted it, and the areas in which the virus spread more than others, as well as cases of death, recovery and cases of infection without symptoms, also, severe and mild cases of infection. All of these results clearly reflect the behavior of the virus to provide a complete scenario for the health authorities so that they can take the necessary procedures.